Applications of Linear Differential Operator on Varying Arguments - Annapoorna, S.; Dileep, L. (Communications in Mathematics and Applications, 2024)
In the present work, using Al-Oboudi operator and Carlson-Shaffer operator, we introduce a new Linear operator \(\mathcal{AS}_{λ, q}^{δ}\). The objective is to define the new subclasses of analytic functions \(\mathcal{VS}_{λ,δ}^{α, β} (a,c,n; q)\), \(\mathcal{VS}_{λ,δ}^{α}(a,c,n;q) \) using the above linear operator and for functions belonging to these classes we obtain coefficient estimates and many more related properties like extreme points, integral means, unified radii results etc.
Keywords: Al-Oboudi q-differential operator; Univalent functions; Analytic functions and Carlson-Shaffer operator; Linear operator